The Influence of Career Path and Compensation on Employee Turnover Intention of PT ABC XYZ Area - Christylia Gita Fairy Lukman; Ratri Wahyuningtyas (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
As one of the banking service providers in Indonesia, PT ABC employs more than 30,000 employees nationwide. As one of the largest banking institutions in the country, PT ABC encounters various challenges, particularly in the area of human resources. The increasing trend of employees leaving the company has led to a higher turnover intention rate at PT ABC compared to its competitors. This elevated intention to resign has become a critical concern for the company, as it directly impacts workplace stability and overall productivity. As a result, retaining employees has become a continuous challenge for the organization. This study aims to examine the influence of career advancement and compensation on employee turnover intention at PT ABC Area XYZ. In this research, career advancement and compensation are considered two key factors that affect employee loyalty. The research adopts a quantitative method with a descriptive approach. The sample consisted of 150 permanent employees of PT ABC Area XYZ, and data were collected using a questionnaire distributed via Google Forms. The data analysis techniques applied in this study include descriptive statistical analysis and the Structural Equation Modeling Partial Least Squares (SEM-PLS) method, using SmartPLS Version 4 software. The findings reveal that career advancement has a negative but statistically insignificant effect on turnover intention, whereas compensation has a significantly negative effect on turnover intention. This research is expected to provide valuable input, particularly for the Human Capital Management department, in developing strategies to retain employees and reduce turnover intention within the company.